Assessing the Role of IFRS for SMEs in Enhancing Accounting Quality and Economic Efficiency Among Architectural Enterprises Somalia (Architecture Image Studies, 2025)
The primary aim of this study was to assess the role of the International Financial Reporting Standards for Small and Medium-sized Entities (IFRS for SMEs) in enhancing accounting quality and economic efficiency among architectural enterprises in Somalia. A quantitative research design with a descriptive and explanatory approach was employed. Data were collected through structured questionnaires administered to 384 respondents selected via stratified random sampling from architectural SMEs operating in major Somali cities. The instrument’s validity and reliability were confirmed through expert review and Cronbach’s alpha coefficients above 0.70. Descriptive statistics, Pearson correlation, and multiple regression analyses were conducted using SPSS version 27 to test the hypothesized relationships among awareness, accounting quality, financial management practices, regulation, and economic efficiency. The results revealed that all independent variables such as awareness of IFRS for SMEs, accounting quality, financial management practices, and regulation had significant and positive effects on economic efficiency (p < 0.05). The model explained 54% of the variance in economic efficiency (R² = 0.540), with regulation emerging as the strongest predictor (β = 0.397, p < 0.001). The findings suggest that improved awareness and informal application of IFRS for SMEs, coupled with sound financial management and supportive regulatory frameworks, substantially enhance the performance and sustainability of architectural firms in Somalia. The study concludes that adopting IFRS for SMEs principles can serve as a strategic instrument for strengthening financial transparency, decision-making, and economic growth in Somalia’s architectural sector.